The Cases of Kasimov and Myshkin: How Spatial Identity Males Some Cities More Mteropolitan than Others - M. I. Tislenko (Сравнительная политика)
In this article the concept of capitalness as a component of spatial identity is observed on the example of small towns Kasimov and Myshkin. The author analyses, why the concept of capitalness has not got full development while in Myshkin it has been able to gain a foothold in the minds of its citizens.